PERANCANGAN MODEL BISNIS USAHA KECIL MENENGAH MENGGUNAKAN PROSES BISNIS IMPROVEMENT FRAMEWORK ( UKM Ardelicious Kitchen Bandung) - Ira Wirasari; Imam Budi (Fakultas Seni Rupa dan Desain ITB, 2022)
Ardelicious Kitchen is a small industry engaged in the culinary field. In the business process, problems arise along with the increase of the number of consumers. This happens because the business management does not have the right business strategy hence experiencing revenue stagnation. Also, consumers are not satisfied with the services. These conditions have caused the business process to run neither effectively nor efficiently. This affects the income generated, and it is therefore important to study business processes using the Business Process Improvement (BPI) Framework. The phases in this study comprise identifying business processes, process validation, time validation, and resource validation of business processes. The results of the proposed analysis have found that 4 factors are needed to overcome problems regarding customer dissatisfaction, i.e., customer response, target market, services, and infrastructure. Furthermore, to overcome this business management problem, a business management design must be made, so that the entire business process can be carried out effectively and precisely and can achieve the previously set business goals.